IMPLEMENTASI QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK MENGUKUR DAN MENINGKATKAN KEPUASAN PELANGGAN PRODUK KARTON BOX PT. DCK (Universitas Esa Unggul, 2017)
PT. DCK is a packaging industries company that focuses on cardboard boxes. Competition between similar companies makes competition even tighter and more competitive in winning over consumers. The existence of these conditions requires PT DCK to improve the quality of services and products to further develop its business, so it is necessary to measure the quality of services and products in order to know the form of services and products that consumers want. By using the Quality Function Deployment method, companies must understand the needs and desires of consumers and translate them into technical characteristics through the formation of a House Of Quality. From the analysis conducted through the pre-introduction of 19 attributes, there are 16 attributes that influence the quality of customer satisfaction. The level of importance with the highest value on the attribute of on-time delivery according to the agreed schedule with a score of 3.82, for the highest technical characteristics that are the priority to be implemented with a value of 13.9% is employee training and evaluation of the highest customer needs with a value of 8.5%, namely There is a guarantee in case of damage and there are 10 competitive position table attributes with low scores compared to competitors.Â Keywords: costumer satisfaction, quality, quality function deployment, house of quality